Fauna of ground-dwelling arthropods in vineyards of Zadar County (Croatia) - Kristijan Franin; Gabrijela Kuštera; Frane Šišeta (Poljoprivreda, 2016)
Farming practices as well as land-use management have a great impact on biodiversity and composition of ground-dwelling arthropods. In this study, abundance and diversity of spiders and epigeic soil insects in three vineyards in Zadar County (Croatia) were researched. In each vineyard 16 pitfall traps were placed, 4 in one row at the distance of 3 m. Samples were taken every fifteen days from the beginning of May till the end of October in 2014. A total of 469 individuals belonging to 6 orders and 23 families were collected. Significant differences were found among arthropod orders. The most abundant taxonomic group was Hymenoptera (38.8%), followed by Coleoptera (31.98%) and Araneae (27.93%). The highest number of specimens (232) was recorded in the integrated vineyard, whereas in the conventional vineyard on karst only 63 individuals were found. However, these results showed significant differences in arthropod assemblage between integrated and conventional vineyards. Richness and diversity (Shannon Diversity Index) were highest in the integrated vineyard (2.36) as opposed to the conventional vineyard Zaton (2.23). Our results confirmed the importance of ground cover, in the particular weeds, on arthropod abundance and diversity.